Dictionary-free hybrid precoders and combiners for mmWave MIMO systems - Mendez-Rial, Roi; Rusu, Cristian; Gonzalez-Prelcic, Nuria; Heath, Robert W. (SPAWC : signal processing advances in wireless communications, 2015)
The high cost and power consumption of the radio frequency chain and data converters at mmWave frequencies introduce hardware limitations into the design of MIMO precoders and combiners. MmWave hybrid precoding overcomes this limitation by dividing the spatial signal processing between the radio frequency and baseband domains. Analog networks of phase shifters have been proposed to implement the radio frequency precoders, since they achieve a good compromise between complexity and performance. In this paper, we propose a low complexity hybrid precoding design for the architecture based on phase shifters. The new method is a greedy algorithm based on the orthogonal matching pursuit algorithm, but replacing the costly correlation operations over a dictionary with the element-wise normalization of the first singular vector of the residual. The main advantage is that the design avoids any assumption on the antenna array geometry. Additionally, numerical results show the superiority of the proposed method in terms of achievable spectral efficiency over other previous solutions.